Experimental exposure to 3-monochloropropane-1,2-diol from the pre-puberty causes damage in sperm production and motility in adulthood - Vieira, Kátia Cristina Melo Tavares; Favareto, Ana Paula Alves (Acta Scientiarum. Biological Sciences, 2017)
3-Monochloropropane-1,2-diol (3-MCPD) is a food contaminant that can be formed during the thermic processing of various foodstuffs. Studies of reproductive toxicology of 3-MCPD are mainly concentrated in the evaluation of possible insults caused by exposure of adult animals. However, the prepuberty might be a period of different susceptibility to chemicals. The aim of this study was to evaluate the effects on reproductive endpoints of the 3-MCPD-exposure prepubertal male rats. Wistar male rats were assigned to 4 groups: control and exposed to 2.5; 5 or 10 mg kg-1 day-1 of 3-MCPD for 30 days by gavage. Testis and epididymis were used for sperm counts and histology analysis. Sertoli cell number and dynamic of the spermatogenesis were evaluated. Sperm were collected from the vas deferens for evaluation of the sperm motility and morphology. Number of sperm with progressive movement, number of Sertoli cells and germ cells and relative daily sperm production were decreased in the groups exposed to 5 and 10 mg kg-1 day-1 of 3-MCPD. Sperm morphology, testicular and epididymal histology were comparable among groups. Results show that 3-MCPD-exposure of rats from prepuberty might cause alterations in spermatogenesis and sperm maturation, similarly to exposure in adulthood.